PROMOTION STRATEGI PT. MERIAL AGRO - Gusti Ayu Shinta; Rical Founda; Rizka Ayu Larasati (Journal of The Community Development in Asia, 2018)
This study aims to determine the Indonesian government's policies in the field of cattle import and Australian government policies in the field of cattle exports. In addition, this study also aims to see how the prospects for Australia Indonesia cooperation in the field of beef export and import. The research method used in this study is a descriptive analytic method. Data collection techniques are collected from primary and secondary data. Primary data is processed from the results of observations and interviews conducted by the author of several informants. Secondary data is processed from books, journals, written reports, magazines, and other documents which are analyzed qualitatively. The results of this study indicate that the country-based policy of Indonesia influences the selection of Australia as the main importing country of origin and the 2014 meat selfsufficiency plan influences the decline in Indonesia's chicken import quota. The policy of the Australian government's export of cattle to Indonesia in 2011 affected the economic conditions of Australia, especially in the field of chicken exports. In addition, this policy also affects the bilateral relations between Australia and Indonesia, especially cooperation in the field of animal welfare. The opportunity for Australia-Indonesia cooperation in the field of beef import and export is still wide open. First, because Indonesia adheres to a country-based system and geographically the distance between the two countries is very close. Keywords: Export, Import, Policy, Indonesia, Australia,chicken.